Self-assembled organic nanomedicine enables ultrastable photo-to-heat converting theranostics in the second near-infrared biowindow - Huijing Xiang (Nature Portfolio, 2021)
Organic agents with activity in the second near infrared region (NIR-II) are needed for precise treatment of cancer. Here, the authors develop boron difluoride formazanate nanosystem as a theranostic agent active in the NIR-II region for treating deep-seated hepatocellular carcinoma in mice.